Arsenic and cadmium leaching in co-contaminated agronomic soil and the influence of high rainfall and amendments. (1st January 2023) - Gunadasa, Sajanee G.; Tighe, Matthew K.; Wilson, Susan C.
Abstract: Arsenic (As) and cadmium (Cd) co-contaminate agricultural systems worldwide and threaten water resources, food security and human health. This column leaching study examined As and Cd mobility in an acidic sandy loam Alfisol soil collected from the dry zone of Sri Lankafor four co-contaminant concentration combinations (spiked and 1 year aged As at 20 & 100 mg kg −1 with co-added Cd at 3 & 20 mg kg −1 ) i, and under the influence of high rainfall (RF), phosphorus fertilizer (P) and lime amendments. In almost all treatments a synergistic co-contaminant adsorption effect was evident which reduced leaching of both elements, significantly in the higher spiked soil concentration treatments. The magnitude of leaching decrease varied with treatment but was greater for As due to its weaker retention in the soil. The co-sorbing effects, evident even under RF, were attributed to electrostatic sorption interactions, the formation of ternary bridging complexes and surface precipitation at higher concentrations. Liming significantly retarded mobilisation of both elements in all treatments, whereas P enhanced As leaching but suppressed Cd leaching, and both amendments moderated co-contaminant effects. An antagonistic effect of Cd on As sorption was evident in two treatments which showed increased As leaching with added Cd: the RF low spike concentration treatment, accredited to washout of stable As–Cd soluble complexes; the P high concentration treatment considered due to P disruption of As–Cd bridging complexes. This work is important for effective risk mitigation in these widely occurring co-contaminated agronomic systems, and demonstrates a strong system effect on synergistic or antagonistic co-contaminant interactions. Graphical abstract: Image 1 Highlights: Synergistic sorption for Cd and As decreased leachate concentrations. Synergistic sorption effects increased with higher soil Cd and As concentrations. Liming enhanced the decrease in As and Cd leached from soil. P fertilizer disrupted synergistic sorption for As but reduced Cd leached. Antagonistic sorption was rarely evident.